A first approximation to the Colombian Amazon basin remnant natural capital. Policy and development implications (2022)
The Amazon basin is one of the most extensive, biodiverse, and dynamic tropical forest ecosystems on the earth. The Colombian Amazon basin occupies an area of approx. 34 million hectares, located in the country's southeast. The literature about the economic valuation of ecosystem services (ES) and the spatial information on remnant natural resources in the Colombian Amazon basin was revised through various information sources to document the earliest approximation to the state, spatial distribution, and economic value of the remnant natural capital at the scale of biomes, specific ecosystems, and political-administrative units. Our assessment estimated a natural capital loss of 18.1 billion $/year (equivalent to 6.7% of Colombian GDP in 2020) and a remnant natural capital worth 153.9 billion $/year (57% of Colombia's GDP in 2020) for eight ecosystem services. This research founds that a potential expansion in extensive and intensive livestock production systems (in a ten-year projection) will generate an additional loss of remnant natural capital of approximately 9.1 billion $/year. Finally, considering that 63% of the remnant natural capital is represented in indigenous reservations and 28% in protected areas, it is essential that the political management of the Amazon Basin concentrate on strengthening these land management figures. Improving the governability of indigenous lands and incentive sustainable agricultural and cattle ranching production, are the principal political challenges.